Collected Essays on the Gospel According to Mark - Yarbro Collins, Adela (Mohr Siebeck, 2023)
Gesammelte Aufsätze zum Markusevangelium.
PublicationDate: 20230208
Keywords: Ancient Judaism -- Graeco-Roman world -- genre studies -- Kartellverfahren -- ancient Judaism -- Neues Testament -- Antike -- Array